Lymph node ratio as a predictor for outcome in oral squamous cell carcinoma: a multicenter population-based cohort study - Spoerl, Steffen; Gerken, Michael; Mamilos, Andreas; Fischer, René; Wolf, Stefanie; Nieberle, Felix; Klingelhöffer, Christoph; Meier, Johannes K.; Spoerl, Silvia; Ettl, Tobias; Reichert, Torsten E.; Spanier, Gerrit (Clinical Oral Investigations, 2020)
Objectives: Recently, multiple studies addressed the importance of lymph node ratio (LNR) in specifying patients’ risk of disease recurrence in various malignancies. The present study examines the prognostic significance of LNR in predicting outcome of oral squamous cell carcinoma (OSCC) patients after surgical treatment with curative intent. Methods: Here, we describe a retrospective population-based cohort with 717 patients previously diagnosed with OSCC. Histopathologically verified lymph node metastasis was diagnosed in 290 patients. Among these patients, we evaluated the impact of LNR on overall survival (OAS) and recurrence-free survival (RFS) in uni- as well as multivariate analysis. Results: A median cutoff (0.055) in LNR was found to significantly predict outcome in OSCC patients. Five-year OAS was 54.1% in patients with a low LNR, whereas a high LNR was associated with a 5-year OAS of 33.3% (p < 0.001). Similar results were detected for RFS with a 5-year survival rate of 49.8% (LNR low) and 30.3% (LNR high) (p = 0.002). Results were confirmed in multivariate Cox regression which substantiated the importance of LNR in predicting survival in OSCC patients. Conclusions: LNR was shown to be an independent prognostic factor for outcome of OSCC in a population-based cohort in uni- as well as multivariate analysis. Hereby, a LNR ≥ 0.055 predicted a shorter OAS and RFS in our cohort. Clinical relevance: Besides established histopathological factors, LNR can be used as a reliable predictor of outcome in OSCC and might therefore be further applied in evaluating adjuvant treatment after resection in curative intention.
CRIS-Team Scopus Importer:2020-08-14
Keywords: Lymph node density; Lymph node ratio; Oral squamous cell carcinoma; Recurrence; Survival